HATARI raising risk awareness. - Śliwerski, Jacek (Software engineering notes.)
As a software system evolves, programmers make changes which sometimes lead to problems. The risk of later problems significantly depends on the location of the change. Which are the locations where changes impose the greatest risk? Our HATARI prototype relates a version history (such as CVS) to a bug database (such as BUGZILLA) to detect those locations where changes have been risky in the past. HATARI makes this risk visible for developers by annotating source code with color bars. Furthermore, HATARI provides views to browse through the most risky locations and to analyze the risk history of a particular location.